Cross sectional echocardiographic demonstration of the mechanisms of abnormal interventricular septal motion in congenital total absence of the left pericardium. Issue 3 (March 1997) - Oki, T.; Tabata, T.; Yamada, H.; Manabe, K.; Fukuda, K.; Abe, M.; Iuchi, A.; Fukuda, N.; Ito, S.
Abstract : OBJECTIVE: To investigate the influence of the absence of the pericardium on the left ventricular wall, particularly on interventricular septal motion, using M mode and cross sectional short axis echocardiography in patients with congenital total absence of the left pericardium. METHODS: 21 patients with, congenital total absence of the left pericardium were divided into three groups according to the interventricular septal motion; systolic type (n = 6) with paradoxical motion during systole, diastolic type (n = 11) with abnormal posterior motion during mid to late diastole, and mixed type (n = 4) with paradoxical motion during systole and abnormal posterior motion during diastole. RESULTS: On cross sectional short axis echocardiograms of the left ventricle, in the diastolic type the degree of angular displacement of the papillary muscles during end diastole to end systole showed excessive anticlockwise rotation about the long axis of the left ventricle without marked anteroposterior displacement. In the systolic type, there was shift of the left ventricle towards the anteromedial portion in systole and towards the posterolateral portion in diastole without significant rotation. There was a significantly positive correlation between the degree of angular displacement and the amplitude of diastolic interventricular septal motion during mid to late diastole in all patients. CONCLUSIONS: There was abnormal interventricular septal motion during systole and diastole in patients with total absence of the left pericardium. Abnormal systolic motion was induced by anteroposterior displacement of the left ventricle, and abnormal diastolic motion by left ventricular rotation about the long axis of the heart during the cardiac cycle. Analysis using cross sectional echocardiography was useful for elucidating the mechanisms of abnormal interventricular septal motion.